Evaluation of the Pap smear and colposcopy as a diagnostic method in cervical intraepithelial neoplasia - Oña, José (2015)
Cervical cancer is the most common malignancy Peruvians. It is possibly one of the leading causes of death in women during their reproductive lives. From there, then, that early diagnosis is a must, because of the magnitude that the problem is in our midst.